A 21st Century Evil: Immunopathology and New Therapies of COVID-19 - Silva, Taylon Felipe; Tomiotto-Pellissier, Fernanda; Sanfelice, Raquel Arruda; Gonçalves, Manoela Daiele; da Silva Bortoleti, Bruna Taciane; Detoni, Mariana Barbosa; Rodrigues, Ana Carolina Jacob; Carloto, Amanda Cristina Machado; Concato, Virgínia Márcia; Siqueira, Elaine da Silva; Costa, Idessania Nazareth; Pavanelli, Wander Rogério; et al. (Frontiers in Immunology, 2020)
Coronavirus Disease 2019 (COVID-19) has been classified as a threat of global dimensions, 26 affecting millions of people and killing thousands. It is caused by SARS-CoV-2 virus, which 27 emerged in the end of 2019 in Wuhan, China, quickly spreading worldwide. COVID-19 is a 28 disease that ranges from fever and breathing difficulty to acute respiratory distress and death, 29 affecting more critically older patients and people with previous comorbidities. SARS-CoV-2 30 uses the angiotensin-converting enzyme 2 (ACE2) receptor and mainly spreads through the 31 respiratory tract, from which it reaches several organs. The immune system of infected patients 32 has demonstrated to suffer important alterations, such as lymphopenia, exhausted lymphocytes, 33 excessive amounts of inflammatory monocytes and macrophages, especially in the lungs, in 34 addition to cytokine storm, which may contribute to its severity and difficulty of establishing 35 an effective treatment. Even though no specific treatment is currently available, several studies 36 have been investigating potential therapeutic strategies, including the use of previously 37 approved drugs and immunotherapy. In this context, this review addresses the interaction 38 between SARS-CoV-2 and the patient’s host immune system during infection, in addition to 39 discussing the main immunopathological mechanisms involved in the development of the 40 disease and potential new therapeutic approaches described until now.